Artist-Teacher Rationale - Shanahan, Breanna (The Canadian Art Teacher / Enseigner les arts au Canada)

(untitled) (Canadian Society for Education through Art / Société canadienne d’éducation par l’art, 2025)
This reflective rationale explores my dual identity as an artist and educator, examining how ADHD-driven material exploration transformed from perceived deficit into creative strength. Working primarily in sculpture and installation art, my practice addresses climate change through anthropological studies of trash and examines gender equity in sport through the lens of lived experience as a female athlete. My work develops in chapters that simmer and evolve over time, like shadows that return and deepen as I grow. As a teacher of sculpture and drawing at the college and university level, my pedagogy is fundamentally shaped by my own artistic journey and the mentors who believed in my resourcefulness rather than simply providing answers. I prioritize giving students varied material experiences and the confidence to explore without premature self-labeling. My teaching philosophy centers on fostering resilient inner voices that tell students, “I can solve problems, I have good ideas”—preparing them to sustain creative practices in a world that often undervalues the arts.